Rancang Bangun Sistem Kontrol dan Monitoring Tekanan Gas Pada Biodigester Berbasis IoT: Analisis Waktu dan Stabilitas Koneksi ESP32 dan ESP32-S3 (Lilygo T Display S3) - Saputra, Oki; Khalil, Fakhrul Irfan; Widhiantari, Ida Ayu (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
This study explores the increasing demand for efficient gas pressure monitoring systems in biodigesters, which play a crucial role in renewable energy production. The primary objective of this research is to design and develop a control and monitoring system based on the Internet of Things (IoT) utilizing the ESP32 and ESP32-S3 (Lilygo T Display S3) microcontrollers. An analysis was conducted to assess the connection duration and stability of both microcontrollers, focusing on the time required to establish a WiFi connection and connect to the Arduino IoT Cloud. The results indicate that the ESP32 achieves an initial WiFi connection time of approximately 10 seconds, with total connection durations ranging from 1 minute 3 seconds to 1 minute 36 seconds, while the ESP32-S3 encounters challenges in maintaining stable connectivity, resulting in total connection times between 1 minute 7 seconds and 1 minute 21 seconds due to certificate validation issues. These findings underscore the importance of selecting the appropriate microcontroller to optimize IoT applications for gas pressure monitoring systems in biodigesters, providing insights for developers and researchers to enhance the efficiency and reliability of renewable energy technologies.